Hot deformation behavior of hard-to-deform Ni-based Alloy. Issue 1 (February 2021) - Lu, X D; Zhang, Y W; Shi, S Y; Wen, B; Su, X; Du, J H
Abstract: The very poor hot workability of hard-to-deform GH4742 alloy is represented in the aspects of very narrow available deformation temperature range, high deformation-resistant force and low thermoplasticity. In this paper, the hot deformation behavior of a Ni-based superalloy was studied in the temperature range of 1060-1160°C and strain rate range of 0.05-0.5 s −1 using hot compression tests. A hot deformation equation is given to characterize the dependence of peak stress on the temperature and strain rate. Results of hot compression test of the GH4742 alloy were indicated that the hot deformation is sensitive to temperature and strain rate. A special heat treatment to change the ingot microstructure is proposed to improve the hot workability of the GH4742 alloy. Modified microstructure induces that the hot deformation flow stress of GH4742 alloy was decreased effectively and hot deformation plasticity was increased obviously.